A comparative study of liver abscess: therapeutic aspiration verses continuous catheter drainage - Chandak, Unmed; Araujo, Prenoy; Mitra, Arti (International Surgery Journal, 2019)
Background: Previously liver abscesses were treated primarily by surgery but with advances in imaging techniques the trend is changing towards use of potent antimicrobials and minimally invasive ultrasound guided interventional procedures and surgery is being done only in selected cases. We conducted this study to find out the feasibility, limitations, effectiveness, outcome and complications of therapeutic needle aspiration and continuous catheter drainage of liver abscess. Methods: This was a hospital based randomized control prospective study in which patients with liver abscess were included. 100 patients of liver abscess selected by simple randomization to 2 groups namely Group A (needle aspiration) or Group B (continuous catheter drainage) undergo the above two interventional procedures. For statistical purposes P value less that 0.05 was taken as statistically significant. Results: This study consisted of 100 patients out of whom there were 78 (78%) males and 22 (22%) females with a M:F ratio of 1:0.28. Single hepatic abscess (75%) was more common than multiple abscesses (25%) and pyogenic abscess (67%) was more common than amoebic abscess (33%). Right lobe of liver was most commonly involved (61%) followed by left lobe (22%). All patients in both the groups were treated successfully and there was no treatment failure in any of the groups. Conclusions: Therapeutic needle aspiration as well as continuous catheter drainage both are equally effective in management of liver abscess but needle aspiration had the advantage of being less expensive, easily available and requiring less hospital stay.